Pengaruh Gaya Kepemimpinan Transformasional, Insentif Finansial Dan Komitmen Organisasional Terhadap Semangat Kerja Karyawan The Stones Legian Bali Hotel - Triyana, I Nyoman Yudi; Wibawa, I Made Artha (E-Jurnal Manajemen; Vol 3 No 11 (2014), 2014)
The purpose of this study was to determine the effect of transformational leadership style, financial incentives and organizational commitment to employee morale The Stones Legian Bali Hotel. This study used a quantitative research by using surveys and questionnaires to 96 respondents. Obtained findings that simultaneous variables of transformational leadership style, financial incentives and organizational commitment has a significant influence on employee morale The Stones Legian Bali Hotel. Other results found that in partial transformational leadership style, financial incentives and organizational commitment has a significant influence on employee morale The Stones Legian Bali Hotel. Finally, transformational leadership style variable is a variable that has the most dominant influence on employee morale The Stones Legian Bali Hotel.
Keywords: Style Transformational Leadership, Financial Incentives, Organizational Commitment, Employee Morale